PENGARUH MODAL DAN LOKASI TERHADAP PENDAPATAN PEDAGANG NASI JINGGO DI KELURAHAN KESIMAN KECAMATAN DENPASAR TIMUR - I Dewa Gde Kresna Wirawan; Ni Putu Devi Arisanthi; Putu Siti Firmani (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to determine: (1) the influence of capital on the income of nasi jinggo traders, (2) the influence of location on the income of nasi jinggo traders, (3) the influence of capital and location on the income of nasi jinggo traders in Kesiman Village, East Denpasar District. This study applies a quantitative approach with a sample size of 35 respondents taken from nasi jinggo traders in Kesiman Village, East Denpasar District. The analysis techniques used are multiple linear analysis and determination test. The results of this study show that (1) the capital variable has a significant effect on income, as evidenced by the results of the t-test of 7.139, exceeding the t-table of 2.034 with a significant value of 0.000 < 0.05; (2) the location variable has a significant influence on income as proven by the results of the t-test of 2.838, exceeding the t-table of 2.034 with a significant value of 0.001 < 0.005; 3) capital and location variables have a significant influence on income as evidenced by the calculated F value of 25.957, exceeding the F table of 3.29 with a significance value of 0.000 < 0.05; (4) The results of the determination coefficient using the Adjusted R Square method state that 59.5% of the capital and location variables have a significant influence on income, while the remaining 40.5% is influenced by other factors that were not included in the research. So the results obtained are that there is a significant influence between capital and location on the income of nasi jinggo traders in Kesiman Village, East Denpasar District.